Rekayasa Piranti Lunak Pengelola Tugas Personil Organisasi Fungsional Kerekayasaan - Ivransa Zuhdi Pane (Ultimatics : Jurnal Teknik Informatika, 2016)
Task manager software is useful to support the management of the assignment of the work programs to personnel, monitoring the progress of the tasks and evaluating the personnel performance in an engineering functional organization. Implementation of this software is expected to increase the personnel productivity as well as to provide inputs for the management, which can be utilized to support further decision making activities. To realize such software, an engineering activity is initialized by firstly analyzing the requirement and designing the operational framework, which is used as the base to construct the functional product in the subsequent implementation phases. Index Terms—software engineering, Engineers, engineering functional organization, prototyping